Urban Heat Islands Significantly Reduced by COVID‐19 Lockdown. Issue 2 (24th January 2022) - Liu, Zihan; Lai, Jiameng; Zhan, Wenfeng; Bechtel, Benjamin; Voogt, James; Quan, Jinling; Hu, Leiqiu; Fu, Peng; Huang, Fan; Li, Long; Guo, Zheng; Li, Jiufeng
Abstract: The significant reduction in human activities during COVID‐19 lockdown is anticipated to substantially influence urban climates, especially urban heat islands (UHIs). However, the UHI variations during lockdown periods remain to be quantified. Based on the MODIS daily land surface temperature and the in‐situ surface air temperature observations, we reveal a substantial decline in both surface and canopy UHIs over 300‐plus megacities in China during lockdown periods compared with reference periods. The surface UHI intensity (UHII) is reduced by 0.25 (one S.D. = 0.22) K in the daytime and by 0.23 (0.20) K at night during lockdown periods. The reductions in canopy UHII reach 0.42 (one S.D. = 0.26) K in the daytime and 0.39 (0.29) K at night. These reductions are mainly due to the near‐unprecedented drop in human activities induced by strict lockdown measures. Our results provide an improved understanding of the urban climate variations during the global pandemic. Plain Language Summary: The outbreak of COVID‐19 has destabilized the global economy and resulted in various impacts on the climate and environment. However, the changes in urban climate during lockdown periods, and particularly in urban heat islands (UHIs), remain largely not known. Using satellite and ground‐based measurements, we find that the surface UHI intensity (UHII) during lockdown periods is reduced by 25% in the daytime and by 20% at night. The reductions in canopy UHII are 36% and 42% during the daytime and nighttime, respectively. These reductions almost certainly result from the significant decrease in human activities induced by strict lockdown measures. Our results provide a fresh perspective of understanding urban climate changes during COVID‐19 lockdown periods. Key Points: Reduced human activities during COVID‐19 lockdown cause a significant decline in both surface and canopy urban heat islands (UHI) intensity over China Surface (canopy) UHI intensity is reduced by 0.25 K (0.42 K) and 0.23 K (0.39 K) on average during the day and night, respectively Impacts of COVID‐19 lockdown UHI intensity depend on hour of day